Clostridium difficile infections in teaching hospital in northern Finland - Marttila-Vaara, M. (M.); Ylipalosaari, P. (P.); Kauma, H. (H.) (Springer Nature, 2019)
Abstract Background: The aim of this study to compare the incidence of Clostridium difficile (CD) infections in the five university hospital districts in Finland based on national register. The clinical findings of CD cases in the Oulu University Hospital (OUH) in one-year cohort were also analyzed. Methods: The numbers of the CD cases from the national register were used for the hospital district comparison. A retrospective cohort study was conducted among all adult (> 16 years) patients treated in the OUH in 2013, who had positive CD toxin B gene test in stools. The selection of the cohort was based on the data from the OUH microbiology laboratory and the clinical characteristics were collected from hospital records. Results: The incidence of CD findings in 2013 was higher in the OUH district than in the other four university hospital districts: 159 vs. 70 to 84 per 100,000 inhabitants. In 2013, 261 patients had CD infection treated in the OUH. The yearly number of CD cases treated in the OUH in 2009–2016 varied between 221 and 287, and the corresponding proportion of positive CD findings out of all samples taken varied from 10.0 to 17.8%. A recurrent infection was seen in 58 patients (22%) while the all-cause 30 day mortality was 7.3%. Conclusions: Diagnostic strategies differed nationally, which may explain the differences in CD incidence between the university hospital districts. In the OUH, no increase in the number of CD infections was seen in 2009–2016. Main characteristics of the patient cohort in the OUH were in harmony with earlier literature.